Musical theatre histories expanding the narrative - Taylor, Millie; Rush, Adam (Bedford Square, London Metheun Drama, 2023)
Musical theatre is often perceived as either a Broadway based art form, or as having separate histories in London and New York. This textbook explores how, in reality, there have been frequent and substantial interactions between the West End and Broadway (and elsewhere) out of which musical theatre has developed, and through which it continues to transform. Musical Theatre: A Transatlantic History depicts the musical as neither American nor British, but both and more. Through multiple thematic 'histories', students are taken on a journey from the art form's European and American origins through to African American influences, the 'Golden Age', the 'British Invasion' and 'Megamusicals'. The authors analyse new models and styles, revival culture and the place of social media in projecting the form into the 21st century. Each chapter offers case studies and key concept boxes to identify, explain, and contextualise key discussions, offering an accessible study of a dynamic and evolving medium. Written and developed for undergraduate students of musical theatre, this introductory textbook provides a newly focused and alternative way of understanding musical theatre history" --Provided by publisher.
Introduction. Why We Tell the Story -- 'Putting it Together' : From Operetta to Poperetta -- 'We Are the Rhythms That Colour Your Song' : From Ragtime to Rap -- 'Waving Through A Window' : From Intertext to Instagram -- 'Easy to be Hard' : From Censorship to Sex -- 'Stand Up' : From Gender Duality to Diversity -- 'Another National Anthem' : From Ourselves to the Other -- 'The World Was Wide Enough' : From Colonial to Corporate Culture -- 'Journey to the Past' : From Revival to Revisal.
Includes bibliographical references and index.
Keywords: Musicals -- History and criticism; Musicals -- England -- London -- History and criticism; Musicals -- New York (State) -- New York -- History and criticism